Systematic Evolution of Optical Bandgap and Local Chemical State in Transparent MgO and HfO2 Resistive Switching Materials. Issue 10 (31st May 2022) - Das, Om Prakash; Pandey, Shivendra Kumar
Abstract : Herein, a comprehensive investigation into the optical, local chemical state, and electrical properties of the less explored magnesium oxide (MgO) are presented for resistive switching data storage applications in reference to the well‐documented hafnium oxide (HfO2 ). The observed local chemical state from X‐ray photoelectron spectroscopy (XPS) analysis yields a nonlattice oxygen peak in O 1s spectra, indicating the resistive switching potential of polycrystalline MgO analogous to the amorphous HfO2 as‐deposited thin films. The optical investigation through UV–visible spectroscopic and photoluminescence examination reveals the high transmissivity of HfO2 (84–98%) and MgO (86–88%) thin films in visible and near‐infrared domains, with a high bandgap of 5.6 and 4.2 eV, respectively, implying the possibility of two distinct stable states essential for resistive switching phenomena. Additionally, the electrical characterization manifests bipolar switching phenomena in HfO2 and MgO metal–oxide–metal stacks with SET transitions at 0.6 and 0.5 V, followed by RESET transitions at −0.6 and −0.5 V, respectively. Both oxides in respective stacks exhibit dominant Ohmic conduction in high‐resistive and low‐resistive regions during positive and negative bias. These observations propose MgO as a preferable resistive switching material for nonvolatile data storage applications, showing similar properties of widely studied HfO2 . Abstract : This contribution presents a comprehensive investigation into the optical, local chemical state, and electrical properties of the less explored magnesium oxide (MgO) for resistive switching data storage applications in reference to the well‐documented hafnium oxide (HfO2 ). This study reveals that MgO has resistive switching capability, a high bandgap, high transmissivity, indicating possible application in emerging nonvolatile resistive memory devices.